2022
DOI: 10.3390/jcm11226784
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prognostic Value of 10 Biochemical Indices at Admission for Prediction Postoperative Myocardial Injury and Hospital Mortality in Patients with Osteoporotic Hip Fracture

Abstract: Aim: To evaluate the prognostic impact at admission of 10 biochemical indices for prediction postoperative myocardial injury (PMI) and/or hospital death in hip fracture (HF) patients. Methods: In 1273 consecutive patients with HF (mean age 82.9 ± 8.7 years, 73.5% women), clinical and laboratory parameters were collected prospectively, and outcomes were recorded. Multiple logistic regression and receiver-operating characteristic analyses (the area under the curve, AUC) were preformed, the number needed to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 202 publications
0
4
0
Order By: Relevance
“…Another research investigation demonstrated that those with a significantly higher plasma anion gap have a poorer clinical outcome and an increased likelihood of dying while in the hospital ( 28 ). Biochemical ionic disturbances, blood urea nitrogen, and total bilirubin levels on admission have also been associated with a poorer prognosis for hip fracture ( 29 ). The SOFA score, a metric for evaluating disease severity in ICU patients, has been linked to an unfavorable outcome in fracture patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another research investigation demonstrated that those with a significantly higher plasma anion gap have a poorer clinical outcome and an increased likelihood of dying while in the hospital ( 28 ). Biochemical ionic disturbances, blood urea nitrogen, and total bilirubin levels on admission have also been associated with a poorer prognosis for hip fracture ( 29 ). The SOFA score, a metric for evaluating disease severity in ICU patients, has been linked to an unfavorable outcome in fracture patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a prospectively collected cohort of 1,256 consecutive patients (older than 65 years) admitted to the Department of Orthopaedics Surgery of our hospital with a HF (mean age 82.9 ± 8.7[SD] years, 50.5 % with cervical fracture, 73.5% females) we analyzed admission levels of PLR and LMR as well as the sociodemographic, clinical and numerous routine laboratory parameters in regard to in-hospital all-cause mortality. Detailed descriptions of this cohort, inclusion and exclusion criteria, have been published in another article [5]. Multivariate stepwise logistic regression analyses were performed with cut-offs for PLR >280 (the fourth quartile) and for LMR <1.1 (the first quartile).…”
Section: Methodsmentioning
confidence: 99%
“…It is also necessary to discuss the limitations associated with the study group. There are papers that appear in which the limitation is still the small size of the study group as well as the very large size of the study group which is difficult to systematize [ 96 , 113 , 140 ]. Therefore, it is currently more difficult and important to complete a representative group that will apply to a random patient [ 25 , 107 , 110 ].…”
Section: Why Is It So Difficult To Determine the Effect Of Vitd On Af...mentioning
confidence: 99%